The Relationship Between Gratitude and Social Support with The Stress of Parents Who Have Children in Need of Special - Mega Rista Saras Ati; Andik Matulessy; Muhammad Farid Rochim (Department of Family and Consumer Sciences, Bogor Agricultural University, 2018)
The purpose of this research is to know the relation between gratitude and social support with the stress of parents who have children in need special. Through random sampling techniques, acquired the subject 30 parents who have children in need specially in Surabaya. This research is the gauge scale gratitude scale, stress and social support scale. Research data were analyzed with regression shows double F = 4.750 and sig = 0.01 means there is a significant relationship between social support and gratitude with the stress of parents who have children in need special. The results of the R square = 0.260 meaning stress parents who have children in need special can be explained by the gratitude and social support of 26%. Next partially gratitude does not correlate with the stress parents of children in need special (partial r = 0.001 with sig = 0.998), and social support proved to be significantly correlated negatively with the stress parents of children in need of special r partial =-0.480 with sig = 0.008